Influence of bio loading and the soil type in slope stability analysis using 2D plaxis - Saarandev, Manogar (2019)
Slope instability has been and is an ongoing problem around the world. It maybe caused by mother nature or due to human activities. As the problems are being solved but as time goes on different types or kind of problems which led to slope stabilization comes up. This research aims to study the cause of slope instabilization with the effects of different types of bio-loadings acting on it and also the type of soil . In this research, by collecting relevant data from the soil investigation the factor of safety (FOS) and other important parameters can be generated using the Plaxis 2D software. The characteristics and the properties of the soil will be noted in detail. Furthermore, the types of soil erosion and also the factors that contribute to such occurrence are described to provide a better image on the situation. Besides that, different kind of soil models are also studied and compared with the Plaxis 2D software. In the methodology part, the ins and outs of the software was explained. The procedures or steps of using the Plaxis 2D software was also explained in detail. The expected result for this research will be used as a guide in solving the issues of slope stabilization with the correct live pole method, loading calculations and also the type of soils being used.